(untitled) (Annals of Medical Research, 2021)
Aim: Periodontal diseases are chronic, inflammatory and infectious diseases. Therefore, periodontal treatment aims to eliminate periodontopathogenic bacteria causing periodontal diseases. The aim of present study was to evaluate the effect of a bacterial end metabolite, acetic acid, on periodontopathogenic bacteria, Streptococcus gordonii and Eikenella corrodens.Material and Method: In present research, Eikenella corrodens (ATCC® 23834™) and Streptococcus gordonii (NCTC 7870) were tested. Acetic acid was used in 5% concentration dissolved in distilled water. Negative control agent was distilled water and positive control agents were 0.012% chlorhexidine, penicillin, tetracycline and ciprofloxacin. The antibacterial efficacy of acetic acid against bacteria was tested via disc-diffusion method, MIC test and minimum bactericidal concentration tests.Results: The inhibition zone of ciprofloxacin, penicillin, tetracycline, CHX and acetic acid against Eikenella corrodens and Streptococcus gordonii were 32 and 37 mm, 16 and 14 mm, 21 and 16 mm, 13 and 17 mm, and 14 and 11 mm respectively. Ciprofloxacin and penicillin inhibited bacterial growth in MIC and MBC tests against both bacteria. MIC tests of acetic acid and chlorhexidine against Eikenella corrodens revealed inhibitory effect at 7.81 µl/mL and 0.97 µl/mL concentrations, respectively. Against Streptococcus gordonii, MIC of acetic acid and chlorhexidine were 1.95 µl/mL and 3.90 µl/mL, respectively.Conclusion: Acetic acid is a bacterial end product and has a daily consumption as vinegar. Due to the antibacterial efficacy against periodontopathogenic bacteria, it can be useful in adjunction to periodontal treatment. Further studies to evaluate clinical use of acetic acid as mouthwash, dentifrice, gel and/or irrigation agent are necessary.Keywords: Acetic Acid; Oral Health; Periodontopathogenic Bacteria; Short Chain Fatty Acids.